2001
DOI: 10.1007/pl00000941
|View full text |Cite
|
Sign up to set email alerts
|

Human Genome and Diseases: Review¶The TSH receptor and its role in thyroid disease

Abstract: The thyrotropin (TSH) receptor plays a preeminent role in thyroid physiology and disease. TSH, acting through the TSH receptor, is the major stimulator of thyroid cell growth, differentiation and function. In Graves' disease, the TSH receptor is the target of stimulating antibodies that cause hyperthyroidism. Although still a topic of debate, the TSH receptor has been implicated in the pathogenesis of the endocrine ophthalmopathy associated with Graves' disease. Blocking antibodies against the TSH receptor are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
85
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(88 citation statements)
references
References 229 publications
(249 reference statements)
0
85
0
3
Order By: Relevance
“…These markers also help in evaluating the differentiation status of thyroid cancers and cell lines (16)(17)(18)(19) (Fig. 1 and Table 3).…”
Section: Papillary Thyroid Cancermentioning
confidence: 99%
“…These markers also help in evaluating the differentiation status of thyroid cancers and cell lines (16)(17)(18)(19) (Fig. 1 and Table 3).…”
Section: Papillary Thyroid Cancermentioning
confidence: 99%
“…Increased circulating activated T cells and thyroid-specific autoantibodies occur in Graves' disease. Antibodies directed against the TSH receptor stimulate thyroid function and lead to glandular overactivity (Kopp 2001). Depending on its severity, Graves' disease is classified as subclinical or overt hyperthyroidism.…”
Section: Introductionmentioning
confidence: 99%
“…However, numerous studies have identified genetic lesions within key components of the TSH receptor (TSHR) signalling pathway in human TNG (Tonacchera et al 2000, Yen et al 2000, Corvilain et al 2001, Kopp 2001. Most mutations have been identified in the TSHR gene, with up to 82% of cases of human TNG having identifiable TSHR mutations (Parma et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Most mutations have been identified in the TSHR gene, with up to 82% of cases of human TNG having identifiable TSHR mutations (Parma et al 1997). These mutations are generally within exon 10 of the TSHR gene, specifically within the transmembrane domain, and a 'hot spot' for gain-of-function mutations has been identified at amino acids 619-650 (Yen et al 2000, Kopp 2001.…”
Section: Introductionmentioning
confidence: 99%